Evidence Against the Causal Relationship Between a Putative Cis-Regulatory Variant of MYH3 and Intramuscular Fat Content in Pigs - Huang, Cong; Zhong, Liepeng; Zou, Xiaoxiao; Huang, Yizhong; Cai, Liping; Ma, Junwu (Frontiers in Veterinary Science, 2021)
Improving meat quality has become the main goal of modern pig breeding. Intramuscular fat content (IMF) is an important trait influencing meat quality of livestock, but the molecular mechanism behind this trait is still unclear. Recently, Cho et al. reported the discovery of the first causal mutation affecting IMF and red flesh color (a*) in pigs, namely XM_013981330.2:g.−1805_−1810del, a 6-bp deletion variant in the porcine MYH3 promoter region. The objective of this study was to reassess the causality of this mutation for its potential commercial application. By Sanger sequencing, we firstly identified several new variants (including a 4-bp deletion) at or near the 6-bp deletion site, which formed four haplotypes in multiple breeds. Unexpectedly, the 6-bp deletion allele, previously determined as the MYH3 Q allele because of its significantly positive effect on IMF and a*, was found not only in Chinese indigenous breeds, but also in four western commercial breeds with relatively lower IMF levels, including Duroc, Large White, Landrace and Pietrain. More surprisingly, we found that the MYH3 Q allele and the haplotypes harboring it had no significant effects on IMF, marbling and color score in three large-scale divergent pig populations: the heterogeneous F6 and F7 pigs and commercial crossbred Duroc × (Landrace × Yorkshire) pigs. Transient transfection analysis in porcine satellite cells showed that the 6-bp deletion variants had a negligible effect on transcription of reporter gene, but could attenuate the MRF (myogenesis regulatory factors)-induced increase in luciferase activity of the MYH3 promoter vector. The MYH3 protein level in muscle did not differ significantly among the haplotype groups. Therefore, our results cannot support the causal relationship between the 6-bp deletion in MYH3 and IMF trait, suggesting that the causal mutation for the IMF QTL on SSC12 needs to be further identified.